Approximate analytical expressions for pulse modulation response of quantum cascade lasers - Yong, K.S.C.; Haldar, Manas Kumar; Webb, Jeffrey Frank (Taylor and Francis Ltd., 2018)
Approximate analytical expressions for turn-on delay, rise time and fall time for pulse modulation of the drive current of quantum cascade lasers are presented. These time expressions are obtained using piece-wise analysis of rate equations. From the analytical expressions, the effects of laser parameters and off and on currents are discussed. A numerical analysis shows reasonable agreement with analytical results. It also confirms the predictions from analytical results. The pulse response is compared with that of near-infrared interband lasers. © 2017 Informa UK Limited, trading as Taylor & Francis Group.